Genetic diversity of Physalis minima L. accessions based on morphological traits - Usaizan, Norhanizan; Abdullah, Nur Ashikin Psyquay; Saleh, Ghizan; Kashiani, Pedram (MedCrave Group, 2019)
Physalis minima L. is a member of Solanaceae family. This plant is commonly found in disturbed area and known as weed in Malaysia. P. minima contains high amount of phenolic, alkaloids and physalin compounds, indicating its potential as medicinal plant. Studies were conducted to analyze diversity and relationship within and among populations based on morphological characteristics. Nineteen populations were collected from 11 states of Peninsular Malaysia. The genetic diversity of germplasm collected was estimated using 16 qualitative and quantitative morphological characteristics. Results showed that the 19 populations of P. minima possessed identical qualitative characteristics. However, significant variations were detected for all quantitative traits measured among the 19 P. minima populations using ANOVA. Based on the variation among quantitative traits, the 19 populations were grouped into five clusters using UPGMA clustering method. This indicates the existence of different heterotic group among these populations. Crosses among populations from different heterotic group can cause high heterosis for important traits in P. minima. This information can be utilized in future breeding program to improve local P. minima varieties in Malaysia.